Kompetencje komunikacyjne w nauczaniu języka polskiego jako obcego na przykładzie tematu zdrowie i higiena - Janda, Małgorzata (Dydaktyka Polonistyczna, 2018)
Foreigners who learn Polish language become acquainted with many important subjects including medical issues. Some of the learners will be medical students in the future and the rest will use Polish in their everyday life. The principal skill that decides about using a foreign language is communication. The issues connected with the terms of health, diseases and preventive treatment are inevitable in the communication process. Not only listening comprehension and speaking about medical issues but also improving lexical competence and keeping in mind grammar structures are parts of communication. In the process of teaching Polish as a foreign language the communication is improved with conversation exercises. Owing to the above mentioned exercises the medical concepts such as human anatomy and physiology, hygiene, diseases and their prevention and treatment are located in the realities of the country of the acquired language. The exercises enrich vocabulary and phraseology, they improve grammatical and phonetic accuracy, they teach accuracy in the communication process – at the doctor’s surgery, at the hospital, at the chemist’s and other health facilities.